Effect of analgesia nociception index monitor-based nociception control on perioperative stress responses during laparoscopic surgery in Trendelenburg position: a randomized controlled trial - Kim, Seung Hyun; Chang, Chul Ho; Lee, Jeong-Rim; Seo, Seok Kyo; Kwon, Young In; Lee, Jae Hoon (Frontiers in Medicine, 2023)
Introduction: The analgesia nociception index (ANI) monitor is a nociception monitoring device based on heart rate variability. We aimed to determine the effect of ANI monitor-based intraoperative nociception control on the perioperative stress response during laparoscopic surgery in the Trendelenburg position.Methods: Altogether, 72 female patients who underwent total laparoscopic hysterectomy were randomized to either the control or ANI group. Intraoperative nociception was controlled by remifentanil administration in a conventional manner (based on blood pressure and heart rate) in the control group and by ANI monitoring in the ANI group. Perioperative stress responses were estimated by measuring the levels of serum catecholamines and catabolic stress hormones at three timepoints: after loss of consciousness, at the end of surgery, and 1 h after the end of surgery.Results: The serum cortisol level at the end of surgery was significantly higher in the ANI group than in the control group (p<0.001), although more remifentanil was administered in the ANI group than in the control group (p<0.001). Changes in the other estimators' levels were comparable between groups during the perioperative period. The hemodynamic profiles during surgery were also significantly different between the two groups. Phenylephrine use to treat hypotension was more common in the ANI group than in the control group (p=0.005). However, postoperative clinical outcomes such as pain and nausea/vomiting did not differ between groups.Conclusion: ANI monitor-based nociception control in laparoscopic surgery in the Trendelenburg position did not improve perioperative stress responses, intraoperative opioid consumption, or postoperative clinical outcomes.Trial registration: This trial is registered at ClinicalTrials.gov (NCT04343638).